Combined effect of established BMI loci on obesity-related traits in an Algerian population sample - Badsi, Manel Nassima (BMC Genet, 2014)
BACKGROUND: Genome-wide association studies have identified variants associated with BMI in populations of European descent. We sought to establish whether genetic variants that are robustly associated with BMI could modulate anthropometric traits and the obesity risk in an Algerian population sample, the ISOR study. The ISOR study of 787 adult subjects (aged between 30 and 64) provided a representative sample of the population living in the city of Oran (north-west of Algeria). We investigated the combined effect of 29 BMI established genetic variants using a genetic predisposition score (GPS) on anthropometric traits and obesity risk in 740 subjects. RESULTS: We found that each additional risk allele in the GPS was associated with an increment in the mean [95% CI] for BMI of 0.15 [0.06 - 0.24] kg/m(2) (p = 0.001). Although the GPS was also associated with higher waist (p = 0.02) and hip (p = 0.02) circumferences, these associations were in fact driven by BMI. The GPS was also associated with an 11% higher risk of obesity (OR [95%CI] = 1.11 [1.05 - 1.18], p = 0.0004). CONCLUSIONS: Our data showed that a GPS comprising 29 BMI established loci developed from Europeans seems to be a valid score in a North African population. Our findings contribute to a better understanding of the genetic susceptibility to obesity in Algeria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12863-014-0128-1) contains supplementary material, which is available to authorized users.